Mechanism underlying the acceleration of pitting corrosion of B30 copper–nickel alloy by Pseudomonas aeruginosa - Li, Huan; Sun, Mingxian; Du, Min; Zheng, Zhenxu; Ma, Li (Frontiers in Microbiology, 2023)
Despite its excellent corrosion resistance, B30 copper–nickel alloy is prone to pitting, particularly when exposed to microorganisms. The mechanism underlying the acceleration of pitting of this alloy is not fully understood. In this study, the acceleration of pitting corrosion of the B30 copper–nickel alloy caused by ubiquitous marine microorganism P. aeruginosa was investigated using surface analysis and electrochemical techniques. The results revealed that P. aeruginosa significantly accelerated the pitting of B30 copper–nickel alloy, with a maximum pitting depth of 1.9 times that of the abiotic control and a significant increase in pitting density. This can be attributed to extracellular electron transfer and copper–ammonia complex production by P.aeruginosa, which accelerates the breakdown of the passivation film.